Springing into Action: Reg2 Negatively Regulates Snf1 Protein Kinase and Facilitates Recovery from Prolonged Glucose Starvation in Saccharomyces cerevisiae - Maziarz, Marcin (Appl Environ Microbiol, 2016)
Glucose is the preferred carbon source for the yeast Saccharomyces cerevisiae. Glucose limitation activates Snf1 protein kinase, a key regulator of energy homeostasis that promotes utilization of alternative carbon sources and enforces energy conservation. Snf1 activation requires phosphorylation of its T-loop threonine (Thr210) by upstream kinases. When glucose is abundant, Snf1 is inhibited by Thr210 dephosphorylation. This involves the function of the type 1 protein phosphatase Glc7, which is targeted to Snf1 by a regulatory subunit, Reg1. The reg1 mutation causes increased Snf1 activity and mimics various aspects of glucose limitation, including slower growth. Reg2 is another Glc7 regulatory subunit encoded by a paralogous gene, REG2. Previous evidence indicated that the reg2 mutation exacerbates the Snf1-dependent slow-growth phenotype caused by reg1, suggesting a link between Reg2 and Snf1. Here, we explore this link in more detail and present evidence that Reg2 contributes to Snf1 Thr210 dephosphorylation. Consistent with this role, Reg2 interacts with wild-type Snf1 but not with nonphosphorylatable Snf1-T210A. Reg2 accumulation increases in a Snf1-dependent manner during prolonged glucose deprivation, and glucose-starved cells lacking Reg2 exhibit delayed Snf1 Thr210 dephosphorylation and slower growth recovery upon glucose replenishment. Accordingly, cells lacking Reg2 are outcompeted by wild-type cells in the course of several glucose starvation/replenishment cycles. Collectively, our results support a model in which Reg2-Glc7 contributes to the negative control of Snf1 in response to glucose refeeding after prolonged starvation. The competitive growth advantage provided by Reg2 underscores the evolutionary significance of this paralog for S. cerevisiae. IMPORTANCE The ability of microorganisms to respond to stress is essential for their survival. However, rapid recovery from stress could be equally crucial in competitive environments. Therefore, a wise stress response program should prepare cells for quick recovery upon reexposure to favorable conditions. Glucose is the preferred carbon source for the yeast S. cerevisiae. Glucose depletion activates the stress response protein kinase Snf1, which functions to limit energy-consuming processes, such as growth. We show that prolonged glucose deprivation also leads to Snf1-dependent accumulation of Reg2 and that this protein helps to inhibit Snf1 and to accelerate growth recovery upon glucose replenishment. Cells lacking Reg2 are readily outcompeted by wild-type cells during glucose depletion/replenishment cycles. Thus, while prolonged glucose deprivation might seem to put yeast cells “on their knees,” concomitant accumulation of Reg2 helps configure the cells into a “sprinter's crouch start position” to spring into action once glucose becomes available.